GLOBALISING AND LOCALISING THE GREAT WAR. (1st November 2017) - Gregory, Adrian
ABSTRACT: This article is intended to suggest an approach to the global history of the First World War that can provide a method of managing the potentially unwieldy concept of global conflict by understanding it through the war's impact on localities. By concentrating on four relatively small but significant cities; Oxford in England, Halifax in Nova Scotia, Jerusalem in Palestine and Verdun in eastern France, which experienced the war in very different ways, it looks at both the movement of people and things and the symbolic interconnectivities that made the war a 'world war'. This local focus helps challenge both the primacy of self-contained national history and the focus on the violent interaction of the opposing sides which are the more normal ways of narrating the war. It does not deny the usefulness of these traditional structures of narration and explanation but suggests that there are different and complementary ways the war can be viewed, which create different emphasis and chronologies.